THE ADVANTAGES OF ORGANIZING INDEPENDENT LEARNING THROUGH MOBILE APPLICATIONS: A CASE STUDY OF FRENCH LANGUAGE LEARNING (International Conference on Education, Psychology and Humanities, 2026)
This study investigates the effectiveness of mobile applications in organizing independent learning among university students studying French as a foreign language. The research aims to evaluate the impact of mobile learning tools on students’ vocabulary acquisition, learning motivation, and autonomous learning skills. An experimental study was conducted with 30 undergraduate students over a six-week period. Data were collected through pre-tests, post-tests, questionnaires, and classroom observations. The findings demonstrate that mobile applications significantly improve students’ language proficiency and encourage greater learner autonomy. The study confirms that mobile technologies can serve as an effective tool for enhancing independent learning in higher education.
Keywords: Mobile learning, French language teaching, autonomous learning, mobile applications, digital education, higher education.